The Effect of Plan Maintenance System and Crew Readiness on the Smooth Operation of MV. Asike Global at PT. Pelayaran Korindo Jakarta - Ambar Muslim; Hanik, Kumila; Astriawati, Ningrum (Pusat Riset dan Inovasi Nasional, 2022)
In ensuring the safety of shipping as a support for the smooth running of ship traffic at sea, it is necessary to have a crew member who is skilled, capable, and skilled. The purpose of this study is to determine the effect of the plan maintenance system and the readiness of the crew on the smooth operation of the MV. Asike Global at PT. Korindo Cruise Jakarta. The method used in this study was descriptive quantitative, where the sample used was 30 people. Sampling technique with saturated sampling. The type of data used is primary and secondary data, where primary data is obtained from questionnaires while secondary from literature and books. Data analysis techniques use Likert scale weighting, regression analysis, correlation coefficient analysis, determinant coefficient analysis, and hypothesis testing both simple and multiple. Based on the analysis and discussion, it shows that there is a positive and significant influence of the plan maintenance system on the smooth running of operations, there is a positive and significant influence of the readiness of the crew on the smooth operation, there is a positive and significant influence of the plan maintenance system and the readiness of the crew on the smooth operation of the MV. Asike Global at PT. Korindo Cruise Jakarta.